2006
DOI: 10.1093/ei/cbj032
|View full text |Cite
|
Sign up to set email alerts
|

The Deterrent Effect of Capital Punishment: Evidence from a “Judicial Experiment”

Abstract: We use panel data for 50 states during the 1960-2000 period to examine the deterrent effect of capital punishment, using the moratorium as a ''judicial experiment.'' We compare murder rates immediately before and after changes in states' death penalty laws, drawing on cross-state variations in the timing and duration of the moratorium. The regression analysis supplementing the beforeand-after comparisons disentangles the effect of lifting the moratorium on murder from the effect of actual executions on murder.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 52 publications
0
74
1
1
Order By: Relevance
“…proposition by running a regression with a "law dummy" indicating the presence of a capital punishment law. First, using data from 1960-2000, Dezhbakhsh & Shepherd (2006) reported that the coefficient on the law dummy was negative (that is, finding deterrence) and statistically significant. DW showed, however, that this result became insignificant when the standard errors were adjusted by clustering and when year fixed effects were added to the regression (as is standard) (see Table 2 of Donohue & Wolfers 2005).…”
Section: A Endogenous State Adoption Of a Death Penalty Statute?mentioning
confidence: 99%
See 2 more Smart Citations
“…proposition by running a regression with a "law dummy" indicating the presence of a capital punishment law. First, using data from 1960-2000, Dezhbakhsh & Shepherd (2006) reported that the coefficient on the law dummy was negative (that is, finding deterrence) and statistically significant. DW showed, however, that this result became insignificant when the standard errors were adjusted by clustering and when year fixed effects were added to the regression (as is standard) (see Table 2 of Donohue & Wolfers 2005).…”
Section: A Endogenous State Adoption Of a Death Penalty Statute?mentioning
confidence: 99%
“…executions (following Dezhbakhsh and Shepherd, 2006), 2) the ratio of executions to either population or murders (following DW), 3) the ratio of executions to prisoners (following KLS), or 4) the ratio of executions to death sentences (following DRS, MG, and Zimmerman).…”
Section: B Modeling the Impact Of Capital Punishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, these studies have exploited the fact that in addition to cross-state differences in sentencing policy, there is also variation over time for individual states in the official sentencing regime, the propensity to seek the death penalty in practice, and the application of the ultimate punishment (Chalfin, Haviland, and Raphael 2013). This literature has generated mixed findings with several prominent papers (e.g., Dezhbakhsh, Rubin, and Shepherd 2003;Mocan and Gittings 2003;Zimmerman 2004Zimmerman , 2006and Dezhbakhsh and Shepherd 2006) finding large and significant deterrence effects, and several equally prominent papers (Katz, Levitt, and Shustorovich 2003;Berk 2005;Donohue andWolfers 2005, 2009; and Kovandzic, Vieraitis, and Paquette-Boots 2009) finding little evidence in favor of deterrence.…”
mentioning
confidence: 99%
“…H. DEZHBAKHSH and J.M. SHEPHERD (2006) find that the abolition of the death penalty was associated with an increase while its reintroduction led to a (smaller) decrease of homicides, but J.J. DONOHUE and J. WOLFERS (2005) using a difference-in-difference approach do not find any evidence in this respect. Moreover, DEZHBAKHSH and J.M.…”
Section: Figure 3: T-statistics Of Rolling Regressionsmentioning
confidence: 97%